2000
DOI: 10.1002/etc.5620190316
|View full text |Cite
|
Sign up to set email alerts
|

Arctic char (Salvelinus alpinus) metallothionein: cDNA sequence, expression, and tissue‐specific inhibition of cadmium‐mediated metallothionein induction by 17β‐estradiol, 4‐OH‐PCB 30, and PCB 104

Abstract: In this study, we haveexamined the basallevel expression and tissue‐specificexpressionpatternsof metallothionein (MT) in Arctic char following metal and E2 (17β‐estradiol) treatment. To study the gene regulation in Arctic char, the two MT isoforms were isolated from a lambda‐ZAP hepatic cDNA library and characterized. Determination of basal MT mRNA and MT expression for 10 different tissues revealed a lack of correlation between MT mRNA and MT levels. The inducibility of MT mRNA and the correlation to resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Previous studies demonstrated that estradiol or endocrine-disruptor chemicals could induce the expression of antioxidant genes, such as GST , but reduce CAT and MT expression [24, 28, 64]. At 14 days, the GST induction relative to the controls was higher in females than males, albeit not significantly so, while the induction of MT and CAT expression was significantly higher in males.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies demonstrated that estradiol or endocrine-disruptor chemicals could induce the expression of antioxidant genes, such as GST , but reduce CAT and MT expression [24, 28, 64]. At 14 days, the GST induction relative to the controls was higher in females than males, albeit not significantly so, while the induction of MT and CAT expression was significantly higher in males.…”
Section: Discussionmentioning
confidence: 91%
“…In both species MT is upregulated towards the end of vitellogenesis [38,39] and is believed to sequester Zn from the liver in order to control the Zn homeostasis once vitellogenesis is over [45]. It has also been shown that E2 functions as an antagonist of MT induction in both rainbow trout [28] and Arctic char [46] further supporting the involvement of MT in reproduction. If Vtg requires Zn for proper tertiary folding, then upregulation of MT by cortisol could lead to a redistribution of Zn from Vtg to MT with degradation of Vtg as a consequence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, oestrogens inhibit metallothionein induction in Arctic char ( Salvelinus alpinus , Salmonidae) exposed to cadmium (Gerpe et al . ). Of greater concern is when the effects of one chemical greatly increase the potency of another chemical.…”
Section: Limitations In Current Methodologies For Assessing Impacts Omentioning
confidence: 97%
“…There is also some evidence suggesting that exposure to one substance can affect exposure to others acting by different mechanisms. For example, oestrogens inhibit metallothionein induction in Arctic char (Salvelinus alpinus, Salmonidae) exposed to cadmium (Gerpe et al 2000). Of greater concern is when the effects of one chemical greatly increase the potency of another chemical.…”
Section: Linking Exposure and Fish Health With Populationrelevant Endmentioning
confidence: 99%